PENGARUH KEPERCAYAAN TERHADAP MINAT INVESTASI OBLIGASI SYARIAH OLEH MAHASISWA UMS - Rafif Adhyasta Azaria Aufa; Handini Nara Padya; Dewi Puspita Sari; Lucky Novandito; Putri Yufi Angraheni (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2024)
Bonds are investments in the form of long-term debt securities that provide returns in the form of interest, but from a sharia perspective they are constructed as profit sharing on these returns. This research aims to find out whether students' beliefs can influence their interest in investing in bonds. This type of research is quantitative research that uses primary student data obtainedby distributing questionnaires to FEB UMS students class 2020 and 2021. The technique used to analyze the data in this research is simple linear regression. The results of this research show that there is an influence between students' self-confidence on their interest in investing in sharia bonds. The magnitude of the influence is less than 25% while the rest is caused by other factors. This research can be used as evaluation material to further increase interest in sharia bond investment, especially within the Islamic University environment.